Patient satisfaction on nursing care: the case of gynecology and obstetrics clinics - Akbas, Meltem (Acta Bioethica, 2019)
Nursing care is an effective factor to allow the quality of health care services to be at a desired level. The ethical principles of justice and honesty are important for improving the quality of nursing care and patient satisfaction. This study determined satisfaction levels for nursing care of patients hospitalized in gynecology and obstetrics clinics of different types of hospitals providing health care services. This is a descriptive and cross-sectional study. The sample consisted of 420 female patients hospitalized in gynecology and obstetrics clinics. The data were collected using the “Patient Socio-demographics Form” and “Newcastle Nursing Care Satisfaction Scale.” The nursing care satisfaction level of the participants according to hospital were as follows: Hospital A 70.68±15.51, Hospital B 70.65±15.17, Hospital C 65.41±16.48, Hospital D 71.39±14.66, and in total 67.2±16.13. There were statistically significant relationships between nursing satisfaction levels of participants based on the hospital, marital status, age, income level, and length of hospital stay. Satisfaction levels of the participants regarding nursing care were above average. While the satisfaction levels were similar based on hospitals, the satisfaction levels for the private hospital, training and research hospital, and university hospital were higher than that of the public hospital.